Permafrost thaw and wildfire: Equally important drivers of boreal tree cover changes in the Taiga Plains, Canada. Issue 4 (22nd February 2016) - Helbig, M.; Pappas, C.; Sonnentag, O.
Abstract: Boreal forests cover vast areas of the permafrost zones of North America, and changes in their composition and structure can lead to pronounced impacts on the regional and global climate. We partition the variation in regional boreal tree cover changes between 2000 and 2014 across the Taiga Plains, Canada, into its main causes: permafrost thaw, wildfire disturbance, and postfire regrowth. Moderate Resolution Imaging Spectroradiometer Percent Tree Cover (PTC) data are used in combination with maps of historic fires, and permafrost and drainage characteristics. We find that permafrost thaw is equally important as fire history to explain PTC changes. At the southern margin of the permafrost zone, PTC loss due to permafrost thaw outweighs PTC gain from postfire regrowth. These findings emphasize the importance of permafrost thaw in controlling regional boreal forest changes over the last decade, which may become more pronounced with rising air temperatures and accelerated permafrost thaw. Key Points: Permafrost thaw and fire are equally important controls on tree cover change in the Taiga Plains Declining tree cover is mostly limited to poorly drained areas at the southern limit of permafrost Boreal tree cover is increasing in areas with more stable discontinuous and continuous permafrost